Progressive Legal Perspective in Providing Legal Protection for Educators.: English - Dewi Asri Yustia; Rika Kurniasari Abdulgani; Leni Widi Mulyani (Journal of Law, Politic and Humanities, 2024)
Education plays an important role in building the civilization of a nation and the development of society. The Indonesian Constitution has guaranteed the implementation of education as stipulated in Article 28 C paragraph (1) of the 1945 Constitution. The government is also obliged to play an active role in the implementation of the national education system in order to improve faith, piety, and noble character in order to educate the nation's life, as the goal of the Indonesian state. It is not easy for a Teacher to provide education to students, on the one hand the Teacher needs to provide an understanding of knowledge and on the other hand the Teacher must provide an understanding of attitude and discipline. One of the cases that occurred was in 2012, when a Teacher took disciplinary action against 4 of his long-haired students by shaving the student's head, but one of the students did not accept the action and reported the teacher actions to his father and then reported the teacher to the Police. Although there are legal rules governing the protection of teachers, there are still legal cases experienced by teachers. Therefore, it is necessary to conduct an assessment with regard to (1) What are the obstacles to legal protection for educators? (2) How does progressive law view legal protections for educators to avoid criminalization? and (3) How is the resolution of conflicts between the Teacher and the student handled when carrying out disciplinary duties.